Evaluation of the relationship between dermatoglyphics and mandibular third molar impaction: A cross-sectional study [version 1; peer review: 2 approved] - Yash Merchant; Seyed Mohammed Riahi; Sameep S. Shetty; Nancy Aggarwal; Ashish Kapoor; Premalatha Shetty; Srikant N. (F1000Research, 2022)
Background: Dermatoglyphics can be utilised in clinical settings to identify those who are more likely to have impacted teeth. Additionally, dermatoglyphics looks to have potential as a non-invasive diagnostic method for predicting the presence or absence of an impacted tooth. The goal of this study was to look at the most common dermatoglyphic pattern in people who had or didn't have an impacted mandibular third molar teeth and see if there was a dermatoglyphic signature. Methods: A cross-sectional study with 180 participants was conducted (90 cases and 90 controls). The rolling impression technique was used to apply blue duplicating ink to participants' fingertips, which was then recorded. There was an increase in the frequency of the whorl-plain pattern in the right-hand ring finger (60%; p=0.028) and left-hand little finger (33.3%; p=0.009), as well as the loop-ulnar pattern in the right-hand middle finger (74.4%; p=0.024) in individuals with a predisposition to the presence of impacted teeth. Results: The left-hand little finger was found to be the most predictive for impaction in a forward stepwise binary logistic regression analysis. Conclusions: Dermatoglyphics could be used as a non-invasive sign to predict whether or not a tooth is affected. Its value comes in early detection, which helps to avoid the surgical problems that come with symptomatic extraction of an impacted tooth.